Teologi Kontekstual dalam Budaya Toraja: Yesus Kristus Lebih Agung dari Tomanurun - Jhon Daeng Maeja (Jurnal Teologi (Journal of Theology), 2025)
Contextual theology is an attempt to contextualize Jesus Christ in different cultures. There have been various attempts to introduce Jesus into the culture. The problem is that caution needed in trying to introduce Jesus into culture. This study aims to explore the concept of Jesus Christ in Torajan culture. The research method used is a literature review. The result showed that Jesus Christ was greater than Tomanurun. Jesus Christ sacrified Himself to save all of the people. While Tomanurun who is believed in the creation story of the Torajan people only saved his people.AbstrakTeologi kontekstual merupakan upaya untuk mengkontekstualisasikan Yesus Kristus dalam berbagai budaya. Sudah ada berbagai usaha untuk memperkenalkan Yesus dalam budaya. Masalah yang muncul ialah diperlukan kehati-hatian dalam upaya untuk memperkenalkan Yesus dalam budaya. Penelitian ini bertujuan untuk mendalami konsep Yesus Kristus dalam budaya Toraja. Metode penelitian yang digunakan ialah kajian pustaka. Hasil penelitian menunjukkan bahwa Yesus Kristus lebih agung dari Tomanurun. Yesus Kristus mengorbankan diri-Nya untuk menyelmatkan manusia. Sedangkan Tomanurun yang dipercaya dalam kisah penciptaan orang Toraja hanya menyelamatkan kaumnya.